On the excitation of the Chandler wobble - Yatskiv, Ya.S. (Кинематика и физика небесных тел, 1997)
The problem of the search for an excitation mechanism of the Chandler wobble is briefly reviewed. One of possible sources of excitation of this wobble is discussed. Зроблено короткий огляд проблеми пошуку механізму збудження чандлерівського руху полюса. Обговорюється одне з можливих джерел збудження такого коливання. Сделан краткий обзор проблемы поиска механизма возбуждения чандлеровского движения полюса. Обсуждается один из возможных источников возбуждения такого колебания.